THE ROLE OF ENDOMETRIOSIS IN THE FEMALE REPRODUCTIVE SYSTEM. - Jumaeva D. R; Temirova D.O. (TADQIQOTLAR, 2025)
The  work  examines  the  female  disease  endometriosis,  its  symptoms,  drug treatment and surgical intervention. Endometriosis is a chronic progressive estrogen-dependent disease, characterized by high prevalence, especially among women with pelvic  pain  (40-80%)  and  infertility  (25-80%).  The  choice  of  methods  for  treating endometriosis is wide, but there is no single approach and it is determined individually, taking into account the goal (treatment of pelvic pain or infertility).